Using TikTok in EFL Class: Students’ Perceptions - Amelinda Olivia Maharani Cahyono; Widya Caterine Perdhani (UNIB Press, 2023)
Tik-Tok is a social media platform with a visible explosive boom in recognition over the last few years from its revolutionary emphasis on short-shape films throughout various topics. This research consequently investigated the junior high school students’ perceptions after they were taught using the TikTok application in English language class. This study used a qualitative methodology, focusing on individual interviews with six selected participants. The participants were selected by using purposeful sampling. All of the participants in this study are of a similar age, come from the same geographical region, speak the same language, and have similar cultural and technological experiences with TikTok. According to the findings, students had positive perceptions of the use of TikTok in English class; The Students perceived that; 1) they could discover new phrases with the aid of using surfing content material in Tik Tok; 2) They could discover numerous content materials created through a couple of content creators and discovered many new phrases through the use of the hashtag; 3) They could gain new words and improve their skills; 4) They could gain new knowledge of various English accents and vocabulary used internationally; 5) They could show their talents, and talk with buddies from different nations and 6) They could gain new terms from TikTok and use them in real-life Situations